2017
DOI: 10.1097/md.0000000000009330
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA expression and their target genes in deep vein thrombosis

Abstract: Background:Clinically, d-dimer is the only established biomarker for the diagnosis of deep vein thrombosis (DVT). However, low specificity discounts its diagnostic value. Several publications have illustrated the differentially expressed circulating microRNAs (miRNAs) and their potential diagnostic values for DVT patients. Therefore, we systematically evaluated present researches and further performed bioinformatics analysis, to provide new insights into the diagnosis and underlying mechanisms of miRNAs in DVT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Through literature retrieval, we found five downregulated miRNAs in LEDVT: miR‐136‐5p, miR‐103a‐3p, miR‐191‐5p, miR‐301a‐3p, and miR‐199b‐3p . RT‐qPCR was then performed to detect their expression in the plasma of 90 acute LEDVT patients and 20 normal controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through literature retrieval, we found five downregulated miRNAs in LEDVT: miR‐136‐5p, miR‐103a‐3p, miR‐191‐5p, miR‐301a‐3p, and miR‐199b‐3p . RT‐qPCR was then performed to detect their expression in the plasma of 90 acute LEDVT patients and 20 normal controls.…”
Section: Resultsmentioning
confidence: 99%
“…Through literature retrieval, we found five downregulated miRNAs in LEDVT: miR-136-5p, miR-103a-3p, miR-191-5p, miR-301a-3p, and miR-199b-3p. 19 RT-qPCR was then performed to detect their expression in the plasma of 90 acute LEDVT patients and 20 normal controls. Expression of miR-136-5p, miR-103a-3p, miR-191-5p, miR-301a-3p, and miR-199b-3p were all decreased in acute LEDVT, among which miR-103a-3p presented with the lowest expression (p < .05) (Figure 1a).…”
Section: Mir-103a-3p Expresses Poorly and Cxcl12 Expresses Highly Imentioning
confidence: 99%
“…The data and analyses in the current study suggest that pathways including TNF, PI3K-Akt, IL-17, Jak-STAT, NF-κB, and MAPK should be considered, as such pathways were correlated with the formation of thrombi according to the KEGG enrichment analysis of the DEGs between the DVT and Blank groups. Previous studies (22,23) have reported that MAPK pathways are related to vascular endothelial venous thrombosis and our colleagues have suggested that resveratrol may exert an in vitro antithrombotic activity by inactivating MAPK signaling pathways (24). Moreover, KEGG analysis of the comparison of the Klf15-siRNA group and the Klf15-NC group indicated that PI3K-Akt play a central role in the regulatory pathway involved in DVT formation.…”
Section: Discussionmentioning
confidence: 80%
“…These include hemophilia A (Sarachana, et al, 2015), aberrant coagulation in sepsis (H. J. , venous thrombosis (Rodriguez-Rius, Lopez, Martinez-Perez, Souto, & Soria, 2020; X. Xiang, et al, 2019), venous thrombo-embolism (Hembrom, et al, 2020;Jiang, et al, 2017), arterial thrombosis (J. Lin, et al, 2016), acute pulmonary embolism (Guo, et al, 2014;Kessler, et al, 2016;Liu, Kang, & Liu, 2018;Xiao, et al, 2011;X.…”
Section: Evidence For a Functional Role Of Mirnas In The Hemostatic Smentioning
confidence: 99%